Measuring Well-Being and Exclusion in Europe's Regions - Kitty Stewart (Luxembourg Income Study (LIS), 2002)
The Lisbon summit of the European Council in March 2000 declared the number of people living in poverty and social exclusion in the European Union to be unacceptable, and called for steps to tackle the issue, beginning with the setting of targets for particular indicators. The targets suggested have been broad in nature but have largely concentrated on national averages. This paper seeks to marry this approach with the EU's traditional focus on regional cohesion, by developing regional indicators of well-being and exclusion for EU countries. It draws on a range of sources to put together indicators in five dimensions of well-being: material wellbeing, health, education and participation in two spheres - productive and social. It explores, first, how far national indicators disguise geographical inequalities in these different dimensions; and second, the extent to which regional performance differs according to which dimension is being examined. At the same time, the paper draws attention to the limits of currently available data, in light of the fact that one key aspect of the Lisbon summit conclusions was a commitment to the collection of better data on poverty and social exclusion in the EU.
Keywords: 330; Lebensqualität; Soziale Isolation; Regionale Disparität; EU-Staaten